Endosonography in the diagnosis and management of pancreatic cysts - Kadiyala, Vivek (World J Gastrointest Endosc, 2015)
Rapid advances in radiologic technology and increased cross-sectional imaging have led to a sharp rise in incidental discoveries of pancreatic cystic lesions. These cystic lesions include non-neoplastic cysts with no risk of malignancy, neoplastic non-mucinous serous cystadenomas with little or no risk of malignancy, as well as neoplastic mucinous cysts and solid pseudopapillary neoplasms both with varying risk of malignancy. Accurate diagnosis is imperative as management is guided by symptoms and risk of malignancy. Endoscopic ultrasound (EUS) allows high resolution evaluation of cyst morphology and precise guidance for fine needle aspiration (FNA) of cyst fluid for cytological, chemical and molecular analysis. Initially, clinical evaluation and radiologic imaging, preferably with magnetic resonance imaging of the pancreas and magnetic resonance cholangiopancreatography, are performed. In asymptomatic patients where diagnosis is unclear and malignant risk is indeterminate, EUS-FNA should be used to confirm the presence or absence of high-risk features, differentiate mucinous from non-mucinous lesions, and diagnose malignancy. After analyzing the cyst fluid for viscosity, cyst fluid carcinoembryonic antigen, amylase, and cyst wall cytology should be obtained. DNA analysis may add useful information in diagnosing mucinous cysts when the previous studies are indeterminate. New molecular biomarkers are being investigated to improve diagnostic capabilities and management decisions in these challenging cystic lesions. Current guidelines recommend surgical pancreatic resection as the standard of care for symptomatic cysts and those with high-risk features associated with malignancy. EUS-guided cyst ablation is a promising minimally invasive, relatively low-risk alternative to both surgery and surveillance.